Antimonene: Mechanical Isolation of Highly Stable Antimonene under Ambient Conditions (Adv. Mater. 30/2016). Issue 30 (5th August 2016) - Ares, Pablo; Aguilar‐Galindo, Fernando; Rodríguez‐San‐Miguel, David; Aldave, Diego A.; Díaz‐Tendero, Sergio; Alcamí, Manuel; Martín, Fernando; Gómez‐Herrero, Julio; Zamora, Félix
Abstract : On page 6332, J. Gómez‐Herrero, F. Zamora, and co‐workers describe the isolation of antimonene, a new allotrope of antimony that consists of a single layer of atoms. They obtain antimonene flakes by the scotch tape method; these flakes are highly stable in ambient conditions and even when immersed in water. The 1.2 eV gap calculated in this study suggests potential applications in optoelectronics.